1992
DOI: 10.1007/bf00301634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of F- on apatite-octacalcium phosphate intergrowth and crystal morphology in a model system of tooth enamel formation

Abstract: In order to study the effect of F- on tooth enamel-like apatite formation, crystal growth experiments were carried out in the presence of 0.1 approximately 2 ppm F- at 37 degrees C and at pH 6.5 in a model system of enamel formation where octacalcium phosphate (OCP) was stable. Morphology changed from long and thin ribbons to small needle-like plates, and the product changed from OCP to apatite with an increase in F- concentration. In the presence of 0.1-1 ppm F-, apatite-OCP intergrowth took place, and crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 22 publications
0
46
0
Order By: Relevance
“…Fluoride can accelerate epitaxial growth of apatite crystals on the OCP precursor, changing the crystal morphology [Moriwaki et al, 1983;Iijima et al, 1992]. Changes in the morphology of apatite crystals grown from unstable supersaturated solution as the result of fluoride addition have also been reported previously by Eanes and Meyer [1977], who reported that the presence of fluoride eliminated the formation of the intermediate OCP phase.…”
Section: Discussionmentioning
confidence: 65%
“…Fluoride can accelerate epitaxial growth of apatite crystals on the OCP precursor, changing the crystal morphology [Moriwaki et al, 1983;Iijima et al, 1992]. Changes in the morphology of apatite crystals grown from unstable supersaturated solution as the result of fluoride addition have also been reported previously by Eanes and Meyer [1977], who reported that the presence of fluoride eliminated the formation of the intermediate OCP phase.…”
Section: Discussionmentioning
confidence: 65%
“…[21][22][23][24] The presence of OCP between HA layers was also detected by HREM in in vitro prepared calcium phosphate phases. [25][26][27] The thickness of these lines would then correspond to the water layer of OCP (0.8 nm). We found variable thicknesses of approximately 1 nm.…”
Section: +mentioning
confidence: 99%
“…This may be due to fluoride-induced conversion of acidic precursors such as amorphous calcium phosphate or octacalcium phosphate to apatite [Iijima et al, 1992]. Perhaps a more likely explanation would be the higher relative supersaturation of tissue fluids with respect to a precipitating fluoridated mineral phase.…”
Section: Crystal Growthmentioning
confidence: 99%
“…These range from amorphous short range order calcium phosphates [Posner, 1985] through brushite-like phases to octacalcium phosphate [Brown et al, 1987;Iijima et al, 1992;Johnsson and Nancollas, 1992]. These are often said to be stabilised by carbonate or magnesium.…”
Section: Initiation Of Precipitation During Secretionmentioning
confidence: 99%